A mapping of young Hindu's views on the appropriateness of the death penalty as a function of circumstances of crime. (March 2016) - Kamble, Shanmukh; Mullet, Etienne
Abstract: Four hundred thirty students from the Hindu community living in the state of Karnataka, India, were presented with realistic scenarios depicting a situation in which a defendant has committed a specified crime, and the circumstances of this crime. They were asked to indicate the extent to which they thought that the death penalty would be an appropriate sentence in each concrete case. Five factors were varied in the scenarios: (a) the severity of the crime (burglary, rape, or homicide), (b) the level to which the defendant's culpability had been established (fully vs. not fully), (c) whether the defendant had expressed compassion/empathy for the victims, (d) the defendant's antecedents (whether he had already committed crimes or not), and (e) the level of criminality in the area in which the crime has been committed (low vs. high). Overall, support for the death penalty was relatively high. As expected, qualitatively different personal positions regarding its appropriateness in realistic cases were found, and these positions were related to field of studies. The majority position (31%) was that appropriateness should mainly depend on the type of crime and of the level to which the defendant's culpability was established. Two contrasting minority positions were found, one in which participants essentially focused on type of crime to judge of appropriateness (20%) and another in which they essentially focused on culpability (21%).